Mindfulness vs. sleep education during autologous hematopoietic cell transplantation for multiple myeloma: Feasibility of a randomized controlled pilot study - Elisabeth C. Henley; Hannah A. Liphart; Keayra J. Morris; Iwalola Awoyinka; Michael R. Irwin; Erin S. Costanzo; Diana Winston; Anita D'Souza; Melinda Stolley; Binod Dhakal; Meera Mohan; Marcelo C. Pasquini; et al. (Contemporary Clinical Trials Communications)
Background: Sleep disturbance is common in patients receiving hematopoietic stem cell transplantation (HCT). Mindfulness-based interventions (MBIs) can improve sleep quality during and following cancer treatment by reducing treatment-related symptoms and enhancing immune function. Methods: We conducted a randomized controlled pilot study investigating the feasibility of implementing Mindfulness Awareness Practices for Insomnia (MAP-I) in patients with multiple myeloma (MM) undergoing autologous HCT. Patients were randomized to receive either MAP-I or a Sleep Health Education (SHE) intervention, both consisting of six videos viewed pre-HCT and three virtual sessions in the two weeks post-HCT. Feasibility was assessed by meeting an enrollment rate of 35% and a retention rate of 85%. Results: We screened 120 patients; 54 (45%) were deemed ineligible and 42 (35%) declined participation. Twenty-four of the 66 eligible patients approached were enrolled into the study (36.4% enrollment rate) and were randomized to either MAP-I or SHE. Seven patients completed the study (29.2% retention rate). Most participants who withdrew consent cited feeling overwhelmed or too sick to continue post-HCT. Amendments were iteratively implemented to increase enrollment and retention rates including addition of a study incentive, modifications to the video timeline, and earlier introduction of the mindfulness instructor. Conclusion: Study results detail challenges and opportunities in retaining patients with MM in a virtual MBI sleep intervention during the peri-transplant period. While enrollment met feasibility criteria, most patients felt too overwhelmed or sick in the peri-transplant period to complete the intervention and associated study tasks. Future research should investigate MBIs at other time points throughout HCT. Trial registration: NCT04271930, 2/17/2020.